MUSLIM INTELLECTUAL THOUGHT IN THE SOCIAL SPHERE: THE CONCEPT OF THE STATE IN POLITICAL THOUGHT AL-FARABI, AL-MAWARDI, IBN KHALDUN - Elyati, Eni (LP2M IAI Al-Khairat Pamekasan, 2024)
This article discusses the concept and urgency of the State for human life and the characteristics of heads of State based on the political thoughts of Al-Farabi, Al-Mawardi, and Ibn Khaldun. Islam, being a religion sprung from Allah, does not limit itself to discussing issues of faith and morality but also delves into all aspects of life, including the government. But it is believed that there is clearly no concept of government or kingship in Islam, nor is there a concept of nation-state in the concept of Islam. Understanding the concept of nation will be easier when we use various angles and viewpoints. Since the verses of the Holy Quran and the Hadith of the Prophet Muhammad do not mention a nation that does not have a ruler. However, we rush to the AlQuran and Hadist when we want to know the organs of that country. Islam is a comprehensive religion that addresses all issues, both external and internal. Issues of ketatanegaraan, including issues of national concept according to Islam, are likely to be addressed in this duniawi. This kind of study is known as library research using a descriptive-qualitative approach. Researchers Al-Farabi, Al-Mawardi, and Ibnu Khaldun set out to fill a gap in our knowledge by analysing the political theories of the three major Islamic thinkers